Bioequivalence and Therapeutic Equivalence of Generic and Brand Bupropion in Adults With Major Depression: A Randomized Clinical Trial. Issue 5 (18th January 2019) - Kharasch, Evan D.; Neiner, Alicia; Kraus, Kristin; Blood, Jane; Stevens, Angela; Schweiger, Julia; Miller, J. Philip; Lenze, Eric J.
Abstract : Controversy persists about bupropion XL 300 mg generic equivalence to brand product. A prospective, randomized, double‐blinded crossover in 70 adults with major depression in stable remission taking any bupropion XL 300 mg tested bioequivalence and therapeutic equivalence of available XL 300 mg products. After a 4‐week lead‐in on patients' existing bupropion, four 6‐week phases evaluated brand and three generics. Patients were uninformed of switching. Drug overencapsulation ensured blinding. There were no differences between any generic and brand, or between generics, in peak plasma concentration (Cmax ) and area under the plasma concentration‐time curve over the 24‐hour dosing interval (AUC0–24 ) for racemic bupropion or major metabolites. All generics met formal bioequivalence criteria for bupropion and metabolites. There were no differences between generics and brand, or between generics, in depression symptoms or side effects, assessed by every 3‐week in‐person interview and daily smartphone‐based self‐report. There were no differences in patients' perceptions of bupropion products. Results show three bupropion XL 300 mg generic products are both bioequivalent and not therapeutically different from brand drug and each other.